Regional differences and dynamic evolution of urban land green use efficiency within the Yangtze river economic belt, China - Cui, Xinghua; Lin, Mingyu; Qiu, Ying (Frontiers in Environmental Science, 2023)
In this study, by using the epsilon-based measure (EBM) model, we calculated the urban land green use efficiency (ULGUE) in the Yangtze River Economic Belt from 2005 to 2019. Further, the temporal and spatial distribution, regional differences and evolution trends of ULGUE in the Yangtze River Economic Belt were investigated in depth by using the Dagum Gini coefficient, Kernel Density estimation and Markov Chain method. The following results were obtained. (1) From the perspective of spatial-temporal evolution, from 2005 to 2019, the ULGUE in the Yangtze River Economic Belt showed a fluctuating upward trend, and it was manifested as diffusion from downstream to middle and upper reaches. (2) From the perspective of regional differences, there was a relatively obvious imbalance of ULGUE within the Yangtze River Economic Belt, but over time, the gap has narrowed. (3) Considering the distribution dynamic evolution, the box diagram and distribution curve of ULGUE in the Yangtze River Economic Belt had a tendency to move to high values, but there was a more obvious phenomenon of spatial polarization. (4) For the part of time and space transfer, the ULGUE within the Yangtze River Economic Belt showed the characteristic of “club convergence”, and the Spatial Markov Chain results showed an obvious “spatial spillover” effect.